Cosolvent and Crowding Effects on the Temperature‐ and Pressure‐Dependent Dissociation Process of the α/β‐Tubulin Heterodimer. Issue 9 (21st March 2019) - Schummel, Paul Hendrik; Anders, Christian; Jaworek, Michel W.; Winter, Roland
Abstract: Tubulin is one of the main components of the cytoskeleton of eukaryotic cells. The formation of microtubules depends strongly on environmental and solution conditions, and has been found to be among the most pressure sensitive processes in vivo . We explored the effects of different types of cosolvents, such as trimethylamine‐ N ‐oxide (TMAO), sucrose and urea, and crowding agents to mimic cell‐like conditions, on the temperature and pressure stability of the building block of microtubules, i. e. the α/β‐tubulin heterodimer. To this end, fluorescence and FTIR spectroscopy, differential scanning and pressure perturbation calorimetry as well as fluorescence anisotropy and correlation spectroscopies were applied. The pressure and temperature of dissociation of α/β‐tubulin as well as the underlying thermodynamic parameters upon dissociation, such as volume and enthalpy changes, have been determined for the different solution conditions. The temperature and pressure of dissociation of the α/β‐tubulin heterodimer and hence its stability increases dramatically in the presence of TMAO and the nanocrowder sucrose. We show that by adjusting the levels of compatible cosolutes and crowders, cells are able to withstand deteriorating effects of pressure even up to the kbar‐range. Abstract : Natural osmolytes such as trimethylamine‐N‐oxide are able to effectively modulate the pressure‐ and temperature‐dependent dissociation behavior of the α/β‐tubulin heterodimer.